Status Logam Berat Merkuri (Hg) Dalam Tanah Pada Kawasan Pengolahan Tambang Emas Di Kelurahan Poboya, Kota Palu - S, Mirdat; B, Isrun (AGROTEKBIS, 2013)
Along with the discovery of several gold prospects area in ​​Central Sulawesi, gold mining had increased both by companies, cooperatives and illegal mining. The activity of this mining produce waste that consist of hazardous toxic substances in which there was a heavy metal such as mercury (Hg). This metal is one of the trace elements that has liquid at room temperature, high specific gravity and power electric conductivity, and a toxic chemical element became a global concern because has significant hazardous effect on human health, wildlife and ecosystems. This study was aims to know the content of mercury in soil around the Poboya’s gold mining. The method used in this study was a survey which describes the actually condition of this area and assess the causes of certain symptoms. In this study measurements, field observations, and laboratory analysis had been done. There step that be noticed in this survey were pre-survey, main survey (sampling) and laboratory analysis. Compose soil sample for laboratory analysis had been collected from several sample point that had been plotting by tactics. The results of this study showed that the content of mercury in all representative soil sample and tailings had highest than threshold. Normally, concentrations of mercury in the soil range from 0.03 ppm (normal) to 0.3 to 0.5 ppm (critics); while concentrations of mercury in soil agricultural areas ranged from 0.057 ppm to 8.19 ppm and in tailings ranged from 84.15 ppm - 575, 16 ppm.